Cobalt enrichment enhances the tolerance of Botryococcus braunii to high concentration of CO2. (February 2020) - Cheng, Pengfei; Muylaert, Koenraad; Cheng, Jay J.; Liu, Hui; Chen, Paul; Addy, Min; Zhou, Chengxu; Yan, Xiaojun; Ruan, Roger
Highlight: Cobalt enrichment enhances the tolerance of B. braunii to high concentration of CO2 . The highest removal efficiency of cobalt by the strain was 87.6% with 5.0% CO2 . LCE of B. braunii in cobalt-rich conditions with 5.0% CO2 was 15.7%. B. braunii culture in cobalt-rich medium can improve LCE and capture CO2 . Abstract: This work mainly studied B. braunii adapted to different CO2 concentrations with cobalt enrichment, and developed a process for CO2 capture, hydrocarbon production and cobalt removal. The results showed that B. braunii favored rapid growth at 5.0% (v/v) CO2, and the highest biomass was 1.89 g.L −1 with 4.5 mg.L −1 of cobalt. Hydrocarbon productivity in high concentration CO2 (5.0% and 10.0%) with cobalt enrichment was higher than that in Chu 13 medium. The change in cobalt removal efficiency mainly corresponded to the growth of B. braunii . The LCE of B. braunii in cobalt-rich with high CO2 concentration (5.0% and 10.0%) was 15.7%, and 14.9%, respectively, which was higher than that in normal medium. CO2 fixation rates were also higher in cobalt enrichment coupled with high CO2 concentration. This study not only provides ideas for the removal of toxic metal cobalt, but also has great potential for CO2 biofixation.